Vibration Analysis of a Single-Cylinder Reciprocating Compressor considering the Coupling Effects of Torsional Vibration - Siyuan Liu; Wanyou Li; Zhijun Shuai; Meilong Chen (Shock and Vibration)
A piston slap is one of the main vibration sources of the reciprocating machinery. Much work has been done in this field, most of which was based on a constant rotating speed. However, in practice, the speed of a crankshaft may always fluctuate due to the uneven load or excitation. The inertia forces of moving components are much different at the fluctuating rotating speed comparing with that at a constant speed. In this paper, the piston slap and the induced vibration are analyzed based on the instantaneous angular speed measured on a single-cylinder reciprocating compressor. Firstly, the dynamics of a crank-connecting rod mechanism is analyzed based on the measured instantaneous angular speed which contains the torsional vibration of the air compressor. The time histories of piston slap impact forces considering and without considering torsional vibration are compared. Then, in order to correlate the piston slap impact with the slap-induced vibration, the corresponding transfer functions between the middle stroke of the outer surface of the cylinder liner and the excitation points are measured. And the excitation force on the main bearing is also taken into account to bring the simulation closer to the experimental results. The effects of a torsional vibration on the vibration of the cylinder liner are analyzed, and the simulation results show that the torsional vibration is a factor that must be taken into account in the vibration analysis of the single-cylinder reciprocating compressor.